Open borders the science and ethics of immigration - Bryan Caplan (New York, NY First Second, 2019)
"American policy-makers have long been locked in a heated battle over whether, how many, and what kind of immigrants to allow to live and work in the country. Those in favor of welcoming more immigrants often cite humanitarian reasons, while those in favor of more restrictive laws argue the need to protect native citizens. But economist Bryan Caplan adds a new, compelling perspective to the immigration debate: He argues that opening all borders could eliminate absolute poverty worldwide and usher in a booming worldwide economy--greatly benefiting humanity. With a clear and conversational tone, exhaustive research, and vibrant illustrations by Zach Weinersmith, Open Borders makes the case for unrestricted immigration easy to follow and hard to deny"--Provided by publisher.
Includes bibliographical references
Keywords: Emigration and immigration--Moral and ethical aspects--Comic books, strips, etc